The Hubble Catalog of Variables - Sokolovsky, K.; Bonanos, A.; Gavras, P.; Yang, M.; Hatzidimitriou, D.; Moretti, M. I.; Karampelas, A.; Bellas-Velidis, I.; Spetsieri, Z.; Pouliasis, E.; Georgantopoulos, I; Charmandaris, V; et al. (2017)
We aim to construct an exceptionally deep (V ≲ 27) catalog of variable objects in selected Galactic and extragalactic fields visited multiple times by the Hubble Space Telescope (HST). While HST observations of some of these fields were searched for specific types of variables before (most notably, the extragalactic Cepheids), we attempt a systematic study of the population of variable objects of all types at the magnitude range not easily accessible with ground-based telescopes. The variability timescales that can be probed range from hours to years depending on how often a particular field has been visited. For source extraction and cross-matching of sources between visits we rely on the Hubble Source Catalog which includes 107 objects detected with WFPC2, ACS, and WFC3 HST instruments. The lightcurves extracted from the HSC are corrected for systematic effects by applying local zero-point corrections and are screened for bad measurements. For each lightcurve we compute variability indices sensitive to a broad range of variability types. The indices characterize the overall lightcurve scatter and smoothness. Candidate variables are selected as having variability index values significantly higher than expected for objects of similar brightness in the given set of observations. The Hubble Catalog of Variables will be released in 2018.
Keywords: Astrophysics - Astrophysics of Galaxies; Astrophysics - Instrumentation and Methods for Astrophysics; Astrophysics - Solar and Stellar Astrophysics